In Vitro Rumen Fermentation and Furans Degradation Potential of Rock Candy Juice and Sugarcane Molasses - Zarnegar, Zohreh; Ebrahimi, Seyed; Naserian, Abbas; Valizadeh, Reza (Indian Journal of Animal Nutrition, 2018)
The present study was conducted to examine the rumen fermentation and furans disappearance potential of rock candy juice (RCJ) and sugarcane molasses (SM). In the first experiment, RCJ was compared with SM by in vitro gas production technique. Presence and disappearance of furans in the liquid substances were also investigated before and at the end of 24 h incubation. In the second experiment, a multi-phasic model was used for the interpretation of gas production profile from molasses, rock candy juice, sugar, barley and corn grains whereas gas production was measured at 2 min. intervals. There was no significant difference between the two treatments in terms of the molar VFA proportion and acetate to propionate ratio. At the end of fermentation, concentration of ammonia nitrogen was lower (P<0.05) in the RCJ compared to SM which supplied more utilizable CP through RCJ fermentation compared to SM. After 24 h of fermentation, concentration of SM and RCJ furans decreased compared to the pre-incubation phase which denoted the microbial degradation of furans during fermentation. In the second experiment, gas production was evaluated after 24 h incubation of SM, RCJ, sugar, barley and corn grains at two-minute intervals using an automated gas measurement system. The gas production was higher (P<0.001) in SM compared to the other treatments. On the other hand, rate of gas production from water-soluble carbohydrate sources ‘b’ was higher compared to the grains with the lowest ‘b’ value observed in SM. RCJ had relatively slower rumen fermentation rate. As the price of RCJ was lower compared to the sucrose, hence, it could be used for partial replacement of grains in the diet of dairy cattle.